Information Technology in Educational Management for the Schools of the Future 1997
DOI: 10.1007/978-0-387-35090-5_13
|View full text |Cite
|
Sign up to set email alerts
|

Administration, management and IT in education

Abstract: This paper examines how computerised Management Information Systems (MISs) can support the information and decisional needs of educational managers. Furthermore, the capabilities of such information systems will de described and discussed together with the benefits of using Information Technology (IT) in managing educational organisations. Section three of the paper describes a small scale piece of research that examined senior educational managers' perceptions and usage of IT in Educational Management (ITEM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…While many advocate MIS implementation and use in schools for purposes of enhanced administrative efficiency and effectiveness (Pits, 1995;Selwood & Visscher, 2007;Taylor, 1997), it appears as if the number of studies that examine the realization of such potential is rather scarce. Studies that explore the effects of MIS use in schools present a dichotomous and imbalanced portrayal; while the majority of studies celebrate the ways in which MIS enhance leadership, management and parental involvement (Blau & Hameiri, 2010;Blau & Presser, 2013;Selwood & Drenoyianni, 1997), only a small number of studies focus on the detrimental consequences of MIS usage, mainly in relation to disempowerment and deprofessionalization of teachers (Tatnall & Davey, 2005;Waring, Wainwright, & Skoumpopoulou, 2011). A study by Selwyn (2011b), which interviewed British school-managers and teachers about the effects of MIS implementation, revealed an interesting finding regarding the disciplinary nature of MIS: A number of school-managers reported that the implementation of MIS had enabled them to install a discourse of accountability in their school's working culture, as 'the transparency of whole school working practices' (Selwyn, 2011b, p. 480) created a stronger sense of responsibility among teachers for their individual work.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While many advocate MIS implementation and use in schools for purposes of enhanced administrative efficiency and effectiveness (Pits, 1995;Selwood & Visscher, 2007;Taylor, 1997), it appears as if the number of studies that examine the realization of such potential is rather scarce. Studies that explore the effects of MIS use in schools present a dichotomous and imbalanced portrayal; while the majority of studies celebrate the ways in which MIS enhance leadership, management and parental involvement (Blau & Hameiri, 2010;Blau & Presser, 2013;Selwood & Drenoyianni, 1997), only a small number of studies focus on the detrimental consequences of MIS usage, mainly in relation to disempowerment and deprofessionalization of teachers (Tatnall & Davey, 2005;Waring, Wainwright, & Skoumpopoulou, 2011). A study by Selwyn (2011b), which interviewed British school-managers and teachers about the effects of MIS implementation, revealed an interesting finding regarding the disciplinary nature of MIS: A number of school-managers reported that the implementation of MIS had enabled them to install a discourse of accountability in their school's working culture, as 'the transparency of whole school working practices' (Selwyn, 2011b, p. 480) created a stronger sense of responsibility among teachers for their individual work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, so far there has been little discussion about the effects that MIS have on their users. Within this limited body of research, studies have mostly focused on the perspectives of head teachers (Blau & Presser, 2013;Haughey, 2003;Selwood & Drenoyianni, 1997). Nevertheless, far too little attention has been given to the perspectives of teachers, who represent the majority of the MIS user base.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst it is difficult to disagree with his first two levels of initiation and expansion Visscher claims that: the third level integration can be "characterised by 'integrated modules' and 'the production of management information'" (Visscher, 1995: p.16); and that the fourth level of stabilisation is characterised by computer assistance reaching its full potential with the focus shifting to systems maintenance and refinement. Selwood & Drenoyianni, (1997) argued that these final two levels were somewhat open to debate and that it was possible that systems, even though they may comprise of "integrated modules" may not be flexible enough to provide information for management decisions (Mitchell and Wild, 1993).…”
Section: Figurementioning
confidence: 99%
“…With the benefit of hindsight Selwood & Drenoyianni, (1997)I suggested that in England and Wales it would appear that the third level of the evolution of CASA was administration -the use of computers to aid school administration and that the fourth level is management -IT being used to aid decision making. The stabilisation level still remained but moved to become the fifth level.…”
Section: Figure 2: Interim Theoretical Model For Progress In Itemmentioning
confidence: 99%
“…Asimismo, destacan su utilidad a la hora de desarrollar actividades de carácter práctico (realización de crucigramas, análisis de imágenes, realización de juegos) o también su apoyo para la atención a alumnos con determinadas necesidades educativas especiales. Al respecto, Selwood (2004), señala que muchas de las tareas docentes pueden hacerse más fácil con el uso eficaz de las TIC. Éstas pueden utilizarse como apoyo a la enseñanza y el aprendizaje, ya que permite la preparación de materiales de una calidad superior y el intercambio y Luis Mariano Urueta-Vélez; Rosa Elisa Martínez-Luna reutilización de los mismos de manera que reduzca el tiempo de preparación.…”
Section: Introductionunclassified